Uso de las técnicas grafoplásticas y su incidencia en el desarrollo de la expresión escrita de los niños de educación inicial de la Unidad Educativa Francisco Huerta Rendón - Buenaire de la Cruz, Nancy Maribel (2022)
The present research work is focused on knowing how plastic graph techniques affect the development of written expresión in children of initial education of the francisco huerta rendon educational unit of the city of Babahoyo. It should be emphasized that through the use of plastic graph techniques, students can acquire the process of developing written expresión in a positive way, for which students in their initial stage Will go through a number of motot activities, the same ones that their purpose is to develop their cognitive, affective and psychomotor maturation. Considering that prewriting are a series of actions necessary to strengthen the development of written expresión in children of the initial stage. Teachers should keep in mind that adequate simulation in children Will help complement the teaching- learning process adequately. A well-stimulated child Will have no difficulty in acquiring written expresión.